Supervisi Pengawas dalam Meningkatkan Profesionalisme Guru PAI di SMPN 6 Sempusari Kaliwates Jember Tahun Pelajaran 2025/2026: Penelitian - Manaf, Bukadin (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The supervisory process of Islamic Religious Education (PAI) teachers at SMPN 6 Sempusari Kaliwates, Jember Regency aims to improve the performance and professionalism of Islamic Religious Education (PAI) teachers. In its implementation, Islamic Religious Education (PAI) supervisors are required to be able to accommodate and improve teacher performance. This study aims to explain the implementation of Islamic Religious Education (PAI) supervisory supervision, supporting and inhibiting factors, and its impact on improving the professionalism of Islamic Religious Education (PAI) teachers at SMPN 6 Sempusari Kaliwates, Jember Regency. This study uses a qualitative approach with data collection techniques through interviews, observation, and documentation, as well as data analysis through data reduction, presentation, and verification. The results of the study indicate that (1) Islamic Religious Education (PAI) supervisors conduct supervision by checking the completeness of administration and the readiness of Islamic Religious Education (PAI) teachers in classroom learning; (2) supporting factors for supervision include teachers' willingness to learn and good evaluations from supervisors, while inhibiting factors are limited access to interesting learning resources and teachers' unpreparedness during supervision; and (3) supervision has an impact on increasing the creativity of Islamic Religious Education (PAI) teachers, thus creating a more conducive learning atmosphere.